Desperately seeking parenthood: neonatal nurses reflect on parental anguish. Issue 13 (4th May 2015) - Green, Janet; Darbyshire, Philip; Adams, Anne; Jackson, Debra
<x xml:space="preserve">Abstract</x> Aim and objective This paper aims to explore the ways in which neonatal nurses understand the experience of parents who have experienced infertility, conceived a baby via in vitro fertilisation and delivered an extremely premature infant. The chance of a poor long‐term outcome for the baby is significant; therefore, parental anguish plays out in the neonatal intensive care. Background Current literature suggests that infertility is a significant issue for ageing women and many couples experience multiple cycles of invitro‐fertilisation (IVF) treatment to achieve a pregnancy. Babies conceived through IVF are more likely to have genetic disorders, and be born prematurely. When the baby is born through IVF and is also born extremely prematurely, it creates a crisis situation for the parents. This paper will focus on the parental anguish of achieving a pregnancy through IVF to see the baby born extremely prematurely (defined as ≤ 24‐week gestation). It will examine parental anguish from caregiver perspective of the neonatal nurse who supports the parents through this very difficult time. Design This study used interviews with neonatal nurses, and drew insights from interpretative phenomenology. Methods This research used a combination of a questionnaire and a series of interviews in a qualitative study informed by phenomenology. The analysis of the interview data involved the creation of key themes following extensive coding of thematic statements and the analysis of the emerging themes. Results This paper outlines the neonatal nurses' understanding of parental anguish and overwhelming sadness in parents whose baby was conceived by IVF, and was also born extremely prematurely. The theme of 'seeking parenthood' was synthesised from two sub‐themes – 'longing for a baby' and 'the desperation to become parents'. Conclusion This study identified that neonatal nurses bear witness to parental anguish as their hopes of taking home a live baby might not be realised. The time, effort and money required to achieve a pregnancy does not mean that the baby will be spared the outcomes of extreme prematurity and the risk factors associated with IVF. The parents may be left empty handed. Therefore, the word precious becomes a metaphor for the IVF baby as the neonatal team try desperately to give the parents their much longed baby. Relevance to clinical practice Delayed child bearing has an impact on fertility, with maternal age having the most impact on the ability to conceive. Babies conceived through IVF technologies have a higher risk of genetic abnormalities and being born prematurely, and this will impact on the neonatal intensive care availability. Extreme prematurity and IVF can significantly impact on the baby's outcome. Witnessing parental anguish can be a major source of stress for the neonatal nurses. Neonatal nurses need to develop strategies not only to help the parents but also to prevent the parents' overwhelming sadness from affecting their ability to function in the neonatal intensive care unit.